The Institutional Synthesis of Local Wisdom and CPR Principles: The Sustainability of Kemiri-Coffee Agroforestry in Kawae Community Forest, Bima - Sulaiman Sulaiman (Journal Research of Social Science, Economics, and Management, 2025)
Bima Regency, West Nusa Tenggara, faces significant environmental degradation due to the widespread conversion of protected forest areas into seasonal corn fields, which increases flood vulnerability. This study analyzes the sustainability of the community-based natural resource management model in the Kawae Block Community Forest (HKm), managed by the Forest Farmers Group (KTH) Oi Rida, by integrating Elinor Ostrom’s Common-Pool Resources (CPR) theory with the local wisdom of Ngaha Aina Ngoho. Using a qualitative descriptive approach with a case study design, data were collected through in-depth interviews, participant observation, and document analysis. The findings indicate that the sustainability of HKm Kawae is driven by two synergistic factors: (1) Economic-Ecological Rationality, where the candlenut-coffee agroforestry model provides stable household income (30–50%) while performing essential ecological functions such as carbon sequestration and water conservation, fulfilling Ostrom’s principle of rule congruence (P2); and (2) Social-Institutional Legitimacy, where the local philosophy of Ngaha Aina Ngoho has been institutionalized into informal rules, strengthening collective compliance, supporting graduated sanctions (P6), and embedding conservation ethics into daily practice. The study concludes that the long-term sustainability of community-based forest management depends not only on technical-economic viability but also on the deliberate integration of local cultural values into governance institutions. This model offers a replicable framework for other regions in NTB and similar contexts facing land-use conflicts and environmental pressure.